Social media and the emergence of reflexiveness as a new capability for open strategy - Joao Baptista; Alex Wilson; Robert D. Galliers; Steve Bynhall (2016)
Social media increases transparency and inclusiveness in organizational strategizing by widening engagement with strategy content and participants. However, our study shows that just relying on the feedback features of social media is not sufficient for an open strategy approach. Instead, emergent feedback from social media use leads to tensions initially between the participatory nature of the technology and extant management practices. Ultimately, these tensions encourage the development of new internal capabilities to appropriate feedback structurally into the organization. We conceptualize the emergence of this new organizational capability as reflexiveness. Further, we suggest that it is the development of this capability that, along with transparency and inclusiveness, explain the shift towards more open forms of strategizing and the potential to move organizations towards stewardship, as a governance model more consistent with open strategizing practices in organizations.